TATA KRAMA DAN ETIKA KOMUNIKASI DI ERA SOCIETY 5.0 - Tuty Mutiah, Mutiah; Fitria Argarini, Vivit (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
The role of etiquette and communication ethics in the Society 5.0 Era, which is characterized by the use of digital and physical technology in everyday life, is discussed in this research. Using qualitative methods and literature studies, this research aims to explore the changes that have occurred in the values of etiquette and communication ethics in society. The focus is to discover and explain the impact of technological developments on social dynamics, taking into account the importance of honesty, integrity and responsibility in communication. In an era where information can spread rapidly, better regulation and understanding of the use of technology is necessary to ensure sustainability and social balance. Apart from that, this research also pays attention to the challenges and implications that arise, and proposes steps to strengthen fundamental values in communication in the Era of Society 5.0. New insights (Stage of the art) on how to deal with the complexity of human and technological interactions, enriching understanding of the role of communication etiquette and ethics in building an inclusive and sustainable society.